The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/mpg.0000000000001186
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Differences in Children From Distinct Socioeconomic Levels Living in the Same Urban Area in Brazil

Abstract: Important differences were observed between the gut microbiota of children living under distinct socioeconomic and environmental conditions within the same city. Our findings suggest that children of high socioeconomic status have less favorable gut microbiota than do children who live in poverty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…A prospective study with 70 patients with cirrhosis analyzed jejunal secretion cultures and observed an association of bacterial overgrowth with acid-suppressive therapy ( P = 0.01) and hypochlorhydria ( P < 0.001); nevertheless, no statistical association was detected between the presence of SBP and bacterial overgrowth or acid-suppressive therapy[ 8 ]. With regard to the microbiota, few studies[ 33 - 35 ] were carried out in Brazil, making interesting the pioneer knowledge of the impact of the PPIs in cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study with 70 patients with cirrhosis analyzed jejunal secretion cultures and observed an association of bacterial overgrowth with acid-suppressive therapy ( P = 0.01) and hypochlorhydria ( P < 0.001); nevertheless, no statistical association was detected between the presence of SBP and bacterial overgrowth or acid-suppressive therapy[ 8 ]. With regard to the microbiota, few studies[ 33 - 35 ] were carried out in Brazil, making interesting the pioneer knowledge of the impact of the PPIs in cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 42 studies, which included more than 2000 participants, were included (Table 1). Relative abundance data were not available for 14 of 42 studies [21,30,[51][52][53][54][55][56][57][58][59][60][61][62]. Most studies were from Asia, Europe, and North America, with 12 studies each.…”
Section: Resultsmentioning
confidence: 99%
“…The standard curve for all of the analyses was created by amplifying a Topo TA plasmid (Invitrogen, ThermoFisher, Waltham, MA, USA) carrying a fragment of the reference gene previously amplified by conventional PCR, and its specificity was confirmed by sequencing and BLAST system alignment. With the molecular mass of the plasmid and insert known, it is possible to calculate the copy number as follows: mass in daltons (g/mol) = (size of double-stranded (ds) product in base pairs (bp)) (330 Da × 2 nucleotides (nt)/bp) [ 29 , 30 , 31 ]. If the copy number and the concentration of the plasmid DNA are known, the number of molecules added to subsequent real-time PCR runs can be calculated, thus providing a standard for determining the copy numbers of specific genes [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…With the molecular mass of the plasmid and insert known, it is possible to calculate the copy number as follows: mass in daltons (g/mol) = (size of double-stranded (ds) product in base pairs (bp)) (330 Da × 2 nucleotides (nt)/bp) [ 29 , 30 , 31 ]. If the copy number and the concentration of the plasmid DNA are known, the number of molecules added to subsequent real-time PCR runs can be calculated, thus providing a standard for determining the copy numbers of specific genes [ 29 , 30 , 31 ]. The real-time PCR results are expressed as log CFU per gram of stool (log CFU/g) using the average number of copies of 16S rRNA genes in each bacterium to normalize the counts [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation